An integrated method for understanding the function of macro-lithic tools. Use wear, 3D and spatial analyses of an Early Upper Palaeolithic assemblage from North Eastern Italy. - Isabella Caricola; Andrea Zupancich; Daniele Moscone; Giuseppina Mutri; Armando Falcucci; Rossella Duches; Marco Peresani; Emanuela Cristiani (PLoS ONE, 2018)
The article presents an original analysis which combines use-wear, 3D modelling and spatial analyses to experimental archaeology in order to investigate Early Upper Palaeolithic flint-knapping gestures and techniques involving the use of macro-lithic tools. In particular, the methodological framework proposed in this paper was applied to the study of Protoaurignacian and Aurignacian macro-tools from Fumane Cave (Verona, Italy). Combining spatial analysis and use wear investigation, both at low and high magnifications, permitted the identification and detailed description of the use-related traces affecting both the hammerstones and retouchers which, at Fumane Cave, were used at different stages during flint tool production. Several experimental activities were performed including core reduction, maintenance, and blank production together with different types of edge retouching. From a methodological perspective, the protocol of analysis permitted to codify specific traces and to produce quantitative data related to their geometry and distribution over the tool's surface, according to the activities and gestures performed. The results obtained allowed a careful investigation of the function and the gestures associated to the use of the macro-lithic tools coming from the Protoaurignacian and Aurignacian levels of Fumane Cave while providing a methodological tool for interpreting different archaeological samples.